Kesetaraan Gender: Analisis Wacana Gender terhadap Tokoh Laki-laki dan Perempuan pada Buku Sejarah Kebudayaan Islam - Pebby Selvira (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The Gender Equality Analysis that was rolled out was inspired by normative Islam without any element of discrimination in the name of gender. Especially when mapping the issue of Islamic Culture History (SKI) which is only connoted and dominated by men thrives in the textbook. The research aims to analyze the content of gender discrimination in Islamic Cultural History (SKI) textbooks with the formulation of gender discrimination issues in the material, illustrations, and rubrics of textbooks. The research is in descriptive-analytical library research. Data analysis uses semantic content analysis with destination, attribution, and statement analysis procedures. The results showed that (1) gender equality of male and female characters in SKI subject matter there is still a spread of gender discrimination in the form of marginalization, subordination, and stereotypes seen when discussing characterization or historical roles there is also language used to benefit the male side, supported by data on the average percentage of class accumulation (males by 85% and females 15%). As a contribution to this research by realizing that the Competency Standards and Basic Competencies of the Ministry of Religion, therefore book publishers and or book writers must pay more attention to gender issues in the implementation of Islamic Cultural History (SKI) textbooks at the Madrasah Ibtidaiyah level.